Rodents as indicators of the climatic conditions during the Middle Pleistocene in the southwestern Mediterranean region: implications for the environment in which hominins lived. Issue 150 (January 2021) - López-García, Juan Manuel; Cuenca-Bescós, Gloria; Galindo-Pellicena, Maria Ángeles; Luzi, Elisa; Berto, Claudio; Lebreton, Loïc; Desclaux, Emmanuel
Abstract: Rodents are a very useful tool in reconstructing the environment of the past, especially owing to their rapid response to climate change, their small home range, and their restricted habitat requirements. They are a highly diverse group of mammals, which have high reproduction rates and as a result can evolve rapidly. The abundance of their microfossil remains in archaeological and paleontological sites permits robust statistical analyses to reconstruct the past climate and environment. Recently, a number of studies have affirmed the need to deepen the climatic characterization of the European Quaternary, the Middle Pleistocene being an important stage for ascertaining how our hominin ancestors lived. The aim of this study is to characterize the climatic conditions in which hominins lived in southwestern Mediterranean Europe during the Middle Pleistocene. To reconstruct these climatic conditions, we apply the bioclimatic model to rodent assemblages from Middle Pleistocene sites with human remains (Caune de l'Arago, Sima de los Huesos, Aroeira cave, Visogliano, Trinchera Galeria, and Mollet cave). Based on the percentage distribution of the species in different climate types and applying multiple linear regressions, we estimated the mean annual temperature, the mean temperature of the coldest month, and the mean temperature of the warmest month. We compared these estimates with data collected over the last 30 years from nearby meteorological stations to obtain the differences with current climate and observe the fluctuations. The climatic conditions obtained from the results of this study show that, while in Iberia mild climatic condition prevailed, in southern France and northeastern Italy harsher weather conditions were indicated. Highlights: Rodents were used as proxies to reconstruct the Middle Pleistocene climate. A bioclimatic model was used to reconstruct temperature climatic parameters. Iberian Peninsula sites were characterized by mild climatic conditions. Climatic conditions in southern France and northeastern Italy were harsh. Hominins were well adapted to diverse climatic conditions.